H24

(P): (\(\dfrac{1}{x-\sqrt{x}}\)+\(\dfrac{1}{\sqrt{x}-1}\)):\(\dfrac{\sqrt{x}+1}{x-2\sqrt{x}+1}\)

a)rút gọn bt P

b) tìm x để P=-1

NT
4 tháng 3 2022 lúc 23:35

a: \(P=\dfrac{1+\sqrt{x}}{\sqrt{x}\left(\sqrt{x}-1\right)}\cdot\dfrac{\left(\sqrt{x}-1\right)^2}{\sqrt{x}+1}=\dfrac{\sqrt{x}-1}{\sqrt{x}}\)

b: Để P=-1 thì \(\sqrt{x}-1=-\sqrt{x}\)

=>x=1/4(nhận)

Bình luận (0)

Các câu hỏi tương tự
YT
Xem chi tiết
LA
Xem chi tiết
H24
Xem chi tiết
MB
Xem chi tiết
KH
Xem chi tiết
TD
Xem chi tiết
MD
Xem chi tiết
GC
Xem chi tiết
NA
Xem chi tiết